ROLE OF CO-OPERATIVE NETWORK FOR THE MANAGEMENT OF BOVINE FEMALE INFERTILITY DISORDERS IN GUJARAT - Joshi, R D; Sutaria, Tarun V. (Animal Reproduction Update, 2023)
The co-operative network in Gujarat, India, has given the livestock sector a new direction for growth. The co-operative sector’s dairy husbandry department not only deals with treatment of ill animals but conducts extensive management programmes for infertility. Various programmes like fertility improvement programmes, calf rearing programme, ration balancing programme, productivity enhancement programme, village awareness progress, and training of artificial inseminators are in operation for fertility enhancement. The present review describes the impact of these programmes on fertility based on collected data from various co-operatives of Gujarat.